El escudo de Aquiles - Soto Ayala, Roberto (Byzantion Nea Hellás, 2015)
The shield of Achilles, the one that Homer describes in extense in chant XVIII of the Iliad, and that is included in one of the most outstanding sections of the poema, invites to look at the world in its richness and complexity, and to reflect over the place of man in the cosmos. The present essay poses, in some comments of the text, some questions that try to penetrate in the world of the poet' s intentions as well as the Hellenic cosmovision of reality in Homer times. It is accompanied by an original reproduction of Hefestus' shield together with the original text of "The Shield of Achilles" of Auden, inspired in Homer, which is a dramatic poem that brings about the representation of the heroic in our times.